A Study of R-Magnitude Dependence in Spatial Orientation of Spin Vectors of SDSS DR-7 Galaxies of Redshift 0.10 < Z < 0.11 - Yadav, Shiv Narayan (Scientific World, 2020)
We present a study of spin vector orientations of 44749 r-magnitude SDSS (Sloan Digital Sky Survey) galaxies having redshift 0.10 to 0.11. The r -magnitudes are observed through 616.5 nm CCD (charge coupled device) filter attached to SDSS telescope located at New Mexico, USA. We have converted two dimensional data to three dimensional galaxy rotation axes. Our aim is to find out non-random effects in the spatial orientation of galaxies. In addition, we wanted to check r-magnitude dependence in the spatial orientation. The expected isotropy distribution curves are obtained by removing the selection effects and performing a random simulation method. In general, spin vector orientations of galaxies is found to be random, supporting Hierarchy model of galaxy formation. A local anisotropy is observed in few samples suggesting a gravitational tidal interaction between neighbor galaxies.